Infrared Spectroscopic Behaviour of Coconut Oil and Groundnut Oil - Sharma, H.K.; Prasad, K. (Asian Journal of Chemistry, 2010)
Simple parameters, viz., specific refraction and infra-red spectroscopy were studied for exploring the possibility of developing the rapid method for the detection of adulteration of groundnut oil in coconut oil as a model study. The study indicated that small variation in the value of specific refraction may not give the desired result but the infrared spectra in the frequency range of 3030- 3000 cm -1 can effectively be utilized for the detection of groundnut oil adulteration in coconut oil.